Hypoxia Inducible Factor-1α in Osteochondral Tissue Engineering - Taheem, Dheraj K. (Tissue Eng Part B Rev, 2020)
Damage to osteochondral (OC) tissues can lead to pain, loss of motility, and progress to osteoarthritis. Tissue engineering approaches offer the possibility of replacing damaged tissues and restoring joint function; however, replicating the spatial and functional heterogeneity of native OC tissue remains a pressing challenge. Chondrocytes in healthy cartilage exist in relatively low-oxygen conditions, while osteoblasts in the underlying bone experience higher oxygen pressures. Such oxygen gradients also exist in the limb bud, where they influence OC tissue development. The cellular response to these spatial variations in oxygen pressure, which is mediated by the hypoxia inducible factor (HIF) pathway, plays a central role in regulating osteo- and chondrogenesis by directing progenitor cell differentiation and promoting and maintaining appropriate extracellular matrix production. Understanding the role of the HIF pathway in OC tissue development may enable new approaches to engineer OC tissue. In this review, we discuss strategies to spatially and temporarily regulate the HIF pathway in progenitor cells to create functional OC tissue for regenerative therapies. IMPACT STATEMENT: Strategies to engineer osteochondral (OC) tissue are limited by the complex and varying microenvironmental conditions in native bone and cartilage. Indeed, native cartilage experiences low-oxygen conditions, while the underlying bone is relatively normoxic. The cellular response to these low-oxygen conditions, which is mediated through the hypoxia inducible factor (HIF) pathway, is known to promote and maintain the chondrocyte phenotype. By using tissue engineering scaffolds to spatially and temporally harness the HIF pathway, it may be possible to improve OC tissue engineering strategies for the regeneration of damaged cartilage and its underlying subchondral bone.